Modular teaching in the development of mendelian genetics problem-solving competence in university students - Vidal Jaimes , Edwin Rubén (2019)
Objective. To determine the effects of modular teaching in the development of Mendelian genetics problem-solving competence in students of Agronomic Engineering at Universidad Nacional Hermilio Valdizan of Huanuco. Methods. Research approach was quantitative, explanatory level, with a quasi- experimental design. It included equivalent groups: Control with expository teaching. Experimental with modular teaching. Each with a sample of 23 students. 16 indicators were evaluated for three dimensions: cognitive, procedural and attitudinal. Students T test and Wilcoxon test were used to validate the hypothesis at p <= 0.05. Results. Cognitively, students who received modular education obtained an average of 14 and 52.1 % corresponding to a good and excellent level. With expository teaching the average was 5.17. 17.4 % corresponding to a regular level of achievement. In problem solving, 34.8 % of modular teaching achieved proficiency level. Attitudinally, no statistical difference was found between the two groups. The two groups highlighted interest in learning and academic responsibility. They achieved with modular teaching competent level 34.8 % and 43.5 %, respectively. Expository teaching for the same level, 26.1 % and 34.8 %. 95.7% considered that the method used developed their competence. Conclusion. Modular teaching significantly improves cognitive and procedural development of Mendelian genetics problem- solving, but not attitudinal.